Pengaruh Pemberian Pendidikan Kesehatan Cuci Tangan Terhadap Tingkat Pengetahuan Dan Perilaku Cuci Tangan Pada Anak Sd Di SDN 4 Lenek Tahun Pelajaran 2021/2022 - Hariawan Junardi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2022)
Healthy living behavior in school settings is the practice of clean and healthy living habits in everyday life both while students are in class and outside the classroom such as students washing their hands with soap, brushing their teeth regularly. Washing hands with soap is scientifically proven to be effective in preventing the spread of infectious diseases such as diarrhea, Upper Respiratory Tract Infections (ARI) and Avian Influenza. The porpuse of the research to determine the effect of hand washing health education on the level of knowledge and hand washing behavior in elementary school children at public alementary school 4 Lenek. The methode of the research is a quantitative research using a pre-experimental approach with the one group pretest-posttest design. The population of this study were 97 students in grades IV, V, and VI at public alementary school 4 Lenek. Sampling using the Slovin formula as many as 49 samples. Data collection using questionnaires and observation sheets. The analysis used is the Wilcoxon test. The result of the research is there is an effect of providing health education on the level of knowledge of hand washing with soap (CTPS) through video media and leaflets on students' knowledge of CTPS with a p value of 0.000. There is an effect of providing health education on the level of handwashing with soap (CTPS) through video media and leaflets on student behavior about CTPS with p value 0.000. The conclusion of the research, There is an Effect of Handwashing Health Education on Knowledge Level and Handwashing Behavior in Elementary School Children at public alementary school 4 Lenek.